PERANCANGAN BUKU CITY GUIDE WISATA CAGAR BUDAYA KOTA SURABAYA MENGGUNAKAN TEKNIK ILUSTRASI PENSIL WARNA GUNA MENINGKATKAN DAYA TARIK WISATAWAN - Sembodo, Kukuh Priyo; Bahruddin, Muhammad; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2016)
The purpose of designing city guide book travel heritage city of Surabaya is to increase the attractiveness of travelers. The study was conducted with qualitative methods of doing interviews, documentation, observation and literature study to get the data used to support the manufacture of the design concept travel guide book heritage city of Surabaya. In the Oxford dictionary of English